Peranan Sistem Pengendalian Internal Piutang Di Masa Covid 19: Studi Kasus Penggunaan Aplikasi Mospay - Septiawan, Agus; Muhsyaf, Saipul Arni; Suryani, Embun (E-Jurnal Akuntansi; Vol 34 No 1 (2024)DO - 10.24843/EJA.2024.v34.i01.p17, 2024)
This research aims to analyze the internal control system for receivables during Covid 19 using the COSO approach. The data collection method uses the case study method and the data collection technique uses triangulation techniques, data analysis uses the Mile and Huberman models. Based on the research results, the role of the internal control system for receivables during the Covid-19 period using the mospay application at PT Enseval Putera Megatrding, Tbk, Mataram branch was overall good. The implications of this research include: Reducing the intensity of salesman and collector visits so that it can reduce the spread of Covid 19, reducing lapping by salesmen or collectors, reducing repayment errors by the finance staff team and reducing outstanding accounts, implementing SOP-DBS-DEV- 003 which relates to mospay payment procedures by customers so that compliance theory can be applied to this research, and improve management decision making for outlets that make purchases. Keywords: Receivable Internal Control System; Covid-19, Mospay Application